SISTEM INFORMASI PRESENSI GURU DAN TENAGA TENDIK BERBASIS WEB UNTUK MENINGKATKAN PELAYANAN KEHADIRAN YANG AKURAT (Studi Kasus: SMK PUI GEGESIK) - Taulani, Taulani; Suarna, Nana; Iin, Iin (JATI (Jurnal Mahasiswa Teknik Informatika), 2022)
The school attendance system is one of the important things to do to record the attendance of teachers and staff at PUI Gegesik Vocational School. Attendance activities so far still use manual attendance. The purpose of this study is to design an information system that processes attendance data. The method used in the development of this software uses the waterfall model. The expected results in this study are to make it easier for principals to monitor teacher performance and discipline in the attendance process, to create a new system and store it in a well-distributed database, to add facilities that can make it easier for teachers to take attendance and make it easier for admins to obtain reports. The quality of this system produces: Correctness (80 %), Efficiency (60 %), Usability (82 %), Integrity (85 %), and Reliability (75 %).